SEKOLAH DIINDONESIA - Slamet Widodo (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2005)
ABSTRACTMany school bUildings are affected by destructive earthquake in Indonesia.This paper presents the current conceptions. re~evant to seismic :~sk forconstruction in urban centre that depends on seismiC hazard, vulnerability andbUilding value. School building as an important education facility is being analyzedhere, the analysis including social economics value, school buildings structuresin Indonesia, construction norms and damage to school buildings in the past.Keywords: Earthquake, school bUildings